RELATIONS BETWEEN SERBIA AND RUSSIA DURING THE UKRAINIAN CRISIS - Trailović, Dragan; Rapaić, Stevan (National interest, 2023)
Serbia and Russia are countries that share a long and complex history of political, economic, and cultural ties. Their relations became even more intricate following the outbreak of the crisis in Ukraine, leading to various implications for broader international relations and, consequently, for the relations between the two states. The confrontation between Russia and the West has presented new challenges for Serbia’s foreign policy, placing it at the crossroads between the strategic goal of joining the EU and its traditional friendship with Russia. This article aims to analyze the situation and present the relations between Serbia and Russia during the crisis in Ukraine. The paper will examine the primary areas of cooperation between the two countries, with a particular focus on their political and economic relations during this period. The paper relies on a range of sources, including official statements and documents, media reports, academic studies, and public opinion surveys.